A Q-methodology analysis of journalists' reflection on learning at work - Marc, Caldwell (Department of Communication Science, University of the Free State, 2011)
Journalism education and training has always suffered from doubts about its actual relevance to the preparation of young journalists entering the industry. It is a doubt encouraged by imaginaries such as the theory-practice dichotomy that suggests that theory can happen in one site of practice, and practice can be found in another; and that there exists a transition from one site to the other. The practice theory of Jean Lave and Etienne Wenger (1991) suggests that practice is primary in both sites; in this case, schools of journalism and the news industry. The concept of legitimate peripheral participation, with its emphasis on situated learning, can be used to build a case for a journalism education focused primarily on building the kinds of learning that make the mentorship found in industry possible and indeed viable. Journalism education then becomes a proper preparation for learning “on the job”. This study used Qmethodology to explore the opinions of journalists' reflections on their most effective learning, and found significant similarities between their experience and the type of learning theory advocated by Lave and Wenger.
Keywords: Journalism; Education; Q-methodology